Axisymmetric drop shape analysis for investigating surface tensions in pendant and sessile drops - Arıkan, Muhammed İkbal (Graduate School, 2025)
Surface tension plays a critical role in numerous interfacial phenomena across scientific and industrial applications, making its accurate measurement essential for advancing material and fluid characterization. This study presents a comprehensive framework for surface tension measurement based on the Axisymmetric Drop Shape Analysis (ADSA) method. It combines a low-cost experimental setup with a custom-developed open-source software solution. The aim of this thesis is to improve measurement accuracy of the low-cost drop shape tensiometers while enhancing accessibility and reproducibility for researchers. A precision-controlled ADSA system is designed and assembled for both sessile and pendant drop configurations, incorporating a high-resolution imaging module, an environmental test chamber and a modular droplet dispensing unit. The imaging setup includes a DSLR camera and adjustable LED backlighting to ensure sharp contrast and edge clarity for drop profile acquisition. Additionally, a pitch–yaw tilt correction platform is integrated to minimize substrate inclination, ensuring axisymmetric droplet shapes crucial for accurate surface tension analysis. During the experimental setup assesment, a continous improvement has been done on identifying and minimizing key sources of error such as optical distortion, camera misalignment, and calibration inaccuracies. A combination of distortion grid correction, stable lighting conditions, and geometric alignment procedures were implemented to ensure the fidelity of drop imaging. Following the experimental setup design, a Python-based software was developed to automate the surface tension measurement process. This tool incorporates advanced image processing steps, including noise filtering, Canny edge detection, and apex detection. Subsequently, the Young–Laplace equation was numerically solved, and theoretical profiles were optimized to best fit the experimental drop contours. The software's modular structure allows researchers to adapt it for various drop types and experimental conditions, and its open-source nature promotes transparency and collaboration within the scientific community. To validate the accuracy and functionality of the system, the surface tension of water–ethanol mixtures varying %0-50 wt was measured. The obtained values showed strong agreement with those reported in the literature which confirmed the system's reliability and precision. This work offers a significant contribution to the field of interfacial science by providing a reliable, cost-effective, and reproducible approach to surface tension measurement. The ADSA platform developed here enables researchers to conduct detailed analyses with high accuracy, while its open-source software lays the groundwork for further improvements. Future research directions include enhancing the system's capability for dynamic measurements and expanding its application to complex fluids and surfactant-laden interfaces. In summary, this study delivers an integrated experimental-computational solution for surface tension analysis supporting the advancement of interfacial engineering and materials research.
Sarkıt ve sapsız damlalardaki yüzey gerilimlerini incelemek için eksenel simetrili damla şekli analizi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2025
Keywords: surface tension; yüzey gerilimi; sessile drops; sapsız damlalar